Jurisprudential principles of the cultural system of the Islamic Republic of Iran - Sabzikaran, Majid (2020)
Our revolution, unlike other movements and revolutions of the twentieth century, which often had economic and political foundations, was a cultural revolution, and we find carefully in the main slogans of the revolution (independence, freedom, republic and Islam) that Apart from the word "republic", which has a socio-political meaning, other slogans show the cultural foundations of this movement. Therefore, the cultural system of the Islamic Republic of Iran can be considered as the identity and manifestation of the Islamic Revolution. The set of right and wrong infrastructures is called the habitual beliefs and mental beliefs of a country and a nation called the cultural system. In this article, which has been written by descriptive-analytical method and library collection method and the use of Quran and authentic jurisprudential books, we have achieved the following results: The main basis of the cultural system of the Islamic Republic in the era of absence based on perspective He is a revolutionary provincial jurist and at the head of it is the architect of Imam Khomeini's revolution. The goals of the cultural system of the Islamic Republic of Iran are divided into short-term, medium-term, and long-term, the main purpose of which is to pay attention to the freedom of Muslims and to promote and export monotheism. The pillar of the cultural system is monotheism and its principles are the branches of religion and its sources are books, traditions, consensus, intellect and tools of the cultural system of seminaries, universities, education, media and artistic tools.